From Passive Bystander to Active Defender: Effectiveness of Project-Based Learning In Transforming Students' Prosocial Behavior In Civic Education - Dhimas Wahyu Pradana; Isnarmi Moeis; Junaidi Indrawadi; Hasrul Piliang (JPI: Jurnal Pustaka Indonesia, 2026)
This study aimed to analyze the effectiveness of Project-Based Learning (PjBL) in promoting the transformation of students' prosocial behavior from passive bystander to active defender in a Civic Education context. The study was motivated by the dominance of passive bystander behavior in Class IX J of SMP Negeri 5 Cilacap, Indonesia, characterized by zero defender action (0%) in pre-intervention observations. A Classroom Action Research (CAR) design following Kemmis and McTaggart (2014) was applied across two cycles with 32 students as subjects. Data were collected via observation rubrics measuring five indicators, field notes, interviews, and cognitive tests, analyzed through descriptive statistics and triangulation. Results demonstrated significant improvements in mean prosocial behavior from 77% (Cycle I) to 89.74% (Cycle II), with aspect-specific gains: cooperation +24.62%, initiative and leadership +16.63%, empathy +9.44%, responsibility +9.44%, and defender action +3.69%. Mean cognitive learning scores increased from 76.25 to 88.75. Analysis through Bandura's Social Cognitive Theory and Salmivalli's Participant Role Approach revealed that individual accountability and role simulation simultaneously activated self-efficacy development, moral disengagement reduction, and observational learning. From a Civic Education perspective, this transformation empirically realizes the concept of justice-oriented citizenship as theorized by Westheimer and Kahne (2004) and the civic dispositions framework of Branson (1998). A critical validity discussion explicitly addressed five internal validity threats and four causality arguments, positioning this study as a methodologically transparent contribution to prosocial behavior intervention research.